Silicon Mitigates Ammonium Toxicity in Cabbage (Brassica campestris L. ssp. pekinensis) ‘Ssamchu’ - Song, Jinnan; Yang, Jingli; Jeong, Byoung Ryong (Frontiers in Sustainable Food Systems, 2022)
NH4+ toxicity hinders the cabbage yield because most subspecies or varieties exhibit extreme sensitivity to NH4+. Current knowledge indicates that silicon (Si) can alleviate or reverse the ammonium toxicity severity. However, few investigations have been conducted on NH4+-stressed cabbage to elucidate the mechanism underlying the Si alleviation. The study described herein analyzes induced physio-chemical changes to explore how Si helps mitigate NH4+ toxicity. We applied one of three NH4+:NO3- ratios (0:100, 50:50, 100:0) at a constant N (13 meq·liter-1) to the cabbage plants, corresponding with two Si treatment levels (0 and 1.0 meq·liter-1). Chlorosis and foliage necrosis along with stunted roots occurred following 100% NH4+ application were ameliorated in the presence of Si. The NH4+ toxicity ratio was reduced accordingly. Similarly, inhibition on the uptake of K and Ca, restricted photosynthesis (chlorophyll, stomatal conductance, Fv/Fm), and accumulation of ROS (O2·-, H2O2), as well as lipid peroxidation (MDA) in NH4+-stressed cabbages were mitigated with added Si. The lower observed oxidative stresses in solely NH4+-treated plants were conferred by the boosted antioxidant enzymes (SOD, CAT). Concomitantly, Si-treated plants showed higher activities of key NH4+ assimilation enzymes (GS, GOGAT, NADH-GDH) and NH4+ content in leaves. However, excessive NH4+ assimilations cause the acidic stress, which has been demonstrated to be the primary cause of NH4+ toxicity. Therefore, further investigation regarding the Si effects on H+ regulation and distribution should be warranted.